Alternative Models of Wage Dispersion. (IMF Working Papers; Working Paper ;, 2005)
We analyze labor market models where the law of one price does not hold-that is, models with equilibrium wage dispersion. We begin by assuming workers are ex ante heterogeneous, and highlight a flaw with this approach: if search is costly, the market shuts down. We then assume workers are homogeneous, but matches are ex post heterogeneous. This model is robust to search costs, and it delivers equilibrium wage dispersion. However, we prove the law of two prices holds: generically, we cannot get more than two wages. We explore several other models, including one combining ex ante and ex post heterogeneity, which is robust and can deliver more than two-point wage distributions.